Antimicrobial activity of Malaysian Donax grandis extracts - Mohd Daud, Jamaluddin; Hashim, Ridzwan; Taher, Muhammad; Mohd Hassan, Husna Hawa (Academic Information Press, 2012)
The present investigation was carried out to evaluate the antibacterial activities of four different parts of Malaysian Donax grandis. Dried fruit, root, leaf and stem powder of D. grandis was successively extracted with hexane, dichloromethane and methanol using Soxhlet method. All extracts were screened for its antibacterial and antifungal activity using agar disc diffusion method. The microorganisms used for antibacterial and antifungal were, Staphylococcus aureus, Bacillus cereus, Psedomonas auraginosa, Escherichia coli, Candida albicans, Candida tropicalis and Candida krusei. Streptomycin (25 μg/disc) and Nystatine (30 μg/disc) was used as standards. The extracts (40 μg/disc) showed antimicrobial activity were subjected to minimum inhibitory concentration assay by two fold dilutions method. Hexane, dichloromethane and methanol extract exhibited in-vitro antimicrobial activity. None of the hexane and dichloromethane extracts showed antifungal activity.